THE PHYSICAL, SENSORY, AND CHEMICAL CHARACTERISTICS OF PATIN FISH (Pangasius hypophthalmus) WITH THE ADDITION OF YELLOW PUMPKIN PUREE (Curcubita moschata) - Novenda Abelia; Dyah Koesoemawardani; Susilawati; Dewi Sartika (Jurnal Agroindustri Berkelanjutan, 2026)
Catfish nugget is a highly nutritious processed product but low in dietary fiber. The addition of pumpkin puree, which is rich in fiber and beta-carotene, is expected to improve the nutritional quality and characteristics of the nugget. This study aimed to determine the effect of pumpkin puree addition on the physical and sensory characteristics of catfish nugget, as well as to identify the appropriate level of puree addition to achieve optimal chemical properties. The study used a Completely Randomized Design (CRD) with a single factor and four replications, consisting of seven levels: 0% (P0), 10% (P1), 15% (P2), 20% (P3), 25% (P4), 30% (P5), and 35% (P6) based on the weight of 200 g of fish. The data were statistically analyzed using Bartlett’s and Tukey’s tests, followed by ANOVA and the Honestly Significant Difference (HSD) test at 1% and 5% significance levels. The results showed that the addition of pumpkin puree significantly affected the sensory properties of both cooked and raw catfish nuggets in scoring tests (texture, taste, aroma, color) and hedonic tests (texture, taste, aroma, color, and overall acceptance). The optimal treatment was P4 (25% pumpkin puree), which yielded the following scoring test results: cooked texture 3.37 (slightly soft), raw texture 3.25 (slightly soft), cooked taste 4.75 (very savory), cooked aroma 3.33 (slightly fishy), raw aroma 3.62 (fishy), and both cooked and raw color 3.54 (yellowish white). The hedonic test scores were: cooked texture 3.64 (liked), raw texture 3.56 (liked), cooked taste 4.46 (very liked), cooked aroma 3.74 (liked), raw aroma 3.62 (liked), color (cooked and raw) 4.00 (liked), overall acceptance (cooked) 4.32 (liked), and overall acceptance (raw) 3.52 (liked). The product also had a hardness of 244.94 gF/cm², moisture content 57.52%, ash content 2.39%, protein content 13.3%, fat content 5.2%, crude fiber 2.2%, total carotenoid 90 µg/g, and antioxidant activity of 1.21%.